Species utilisation preferences and resource potential of miombo woodlands : a case of selected villages in Tabora, Tanzania - Mbwambo, Lawrence Richard (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.